Prophylactic ketamine to prevent shivering in parturients undergoing Cesarean delivery during spinal anesthesia - (:unkn) unknown (ELSEVIER SCIENCE INC, 2013)
Study Objective: To compare the efficacy and safety of ketamine 0.25 mg/kg with ketamine 0.5 mg/kg to prevent shivering in patients undergoing Cesarean delivery. Design: Prospective, randomized, double-blinded, placebo-controlled study. Setting: Operating rooms and postoperative recovery rooms. Patients: 120 ASA physical status 1 and 2 pregnant women scheduled for Cesarean delivery during spinal anesthesia. Measurements: Patient characteristics, anesthetic and surgical details, Apgar scores at 1 and 5 minutes, and side effects of the study drugs were recorded. Heart rate, mean arterial pressure, oxygen saturation via pulse oximetry, tympanic temperature, severity of shivering, and degree of sedation were recorded before intrathecal injection and thereafter every 5 minutes. Patients were randomized to three groups: saline (Group C, n=30), intravenous (IV) ketamine 0.25 mg/kg (Group K-0.25, n=30), or IV ketamine 0.5 mg/kg (Group K-0.5, n=30). Grade 3 or 4 shivering was treated with IV meperidine 25 mg and the prophylaxis was regarded as ineffective. Main Results: The number of shivering patients was significantly less in Group K-0.25 and in Group K-0.5 than in Group C (P = 0.001, P = 0.001, respectively). The tympanic temperature values of Group C were lower at all times of the study than in either ketamine group. Median sedation scores of Group K-0.5 were significantly higher than in Group K-0.25 or Group C at 10, 20, 30, and 40 minutes after spinal anesthesia. Conclusions: Prophylactic IV ketamine 0.25 mg/kg was as effective as IV ketamine 0.5 mg/kg in preventing shivering in patients undergoing Cesarean section during spinal anesthesia. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Anesthesia, obstetric; Cesarean section; Ketamine; Shivering, spinal anesthesia; EPIDURAL-ANESTHESIA; REGIONAL ANESTHESIA; MEPERIDINE; MIDAZOLAM